The Adsorption of Copper from Aqueous Solutions Using Acrylamide-Grafted Cellulose - Shahri, M.M.; Ahmad @ Ayob, Mansor; Haron, Md. Jelas; Ab. Rahman, Mohamad Zaki (David Publishing, 2010)
In the present study, the aptitudes of acrylamide grafted cellulose to remove Cu(II) ions from aqueous solutions were investigated. The preparation process was carried out through graft copolymerization of acrylamide onto cellulose, using ceric ammonium nitrate as an initiator. Fourier transform Infrared spectroscopy was used to confirm and characterization polyacrylamide-grafted cellulose formation. Batch experiments of Cu(II) ions adsorption on the grafted cellulose adsorbent were performed. Effects of initial pH of the solution, contact time and initial Cu(II) concentration on the adsorption of Cu(II) were studied. The maximum adsorption of Cu(II) ion on grafted cellulose is observed 90 mg/g at the initial pH of 6. Equilibrium time was reached within 3h. Kinetic data were analyzed using the pseudo-first-order, pseudo-second-order equations. The data fitted very well to the pseudo-second-order rate expression. The equilibrium data for adsorption isotherms of these metal ions on grafted cellulose were obtained using the Langmuir and Freundlich models and the Langmuir model was obtained to be in better correlation with the experimental data. The results showed that acrylamide-g-cellulose developed in this study could be an economical and effective adsorbent for application in removal of copper ion from water and waste waters.